Evaluation of the Effect of Exercise on Depression, Sleep Disorder, Kinesiophobia, Pain and Quality of Life in Cervicomyofascial Pain - Taşkın, Aslıhan; Deniz, Gülnihal; Orhan, Serdar; Gülkesen, Arıf (My University, 2024)
This study was conducted to investigate the effects of exercise on pain, depression, kinesiophobia, sleep disturbance, and quality of life in individuals with myofascial pain syndrome (MAS). This study is a before-after interventional study. Ultrasound, transcutaneous electrical nerve stimulation (TENS), hot pack, head-neck-upper extremity strengthening exercises, stretching and posture exercises were applied to 20 patients with MAS (32-57 years old) (90 minutes/5 days/3 weeks) under the control of a physiotherapist. Visual Analogue Scale (VAS), Neck Disability Index (NDI), Kinesiophobia Scale (Tampa), Bournemouth Neck Questionnaire (BNQ), Nottingham Health Profile (NHP), Beck Depression Inventory (BDI), and Pittsburgh Sleep Quality Index (PSQI) scales were applied as pretest and posttest. It has been seen that exercise effectively reduces neck pain and clinical improvement, significantly reducing depression, improving sleep disorder, improving sleep quality, and increasing perceived health status and effectiveness in activities of daily living (p<0.01). It can be said that exercise applied in patients with MAS improves depression, sleep disturbance, kinesiophobia, pain, and quality of life.
Keywords: Sağlık Bilimleri ve Hizmetleri; Romatoloji; Psikoloji